Management of chronic viral hepatitis in the hematological patient. Issue 3 (4th March 2018) - Nicolini, Laura Ambra; Zappulo, Emanuela; Viscoli, Claudio; Mikulska, Malgorzata
ABSTRACT: Introduction : Infection with HBV and HCV represents a growing challenge in the management of patients with hematological malignancies. Recently, hepatitis E (HEV) was recognized as an endemic infection in developed countries and as an emerging health problem in immunocompromised patients. Areas covered : We reviewed the current knowledge on the impact of chronic viral hepatitis in the hematological setting. Epidemiological features, screening strategies and indications for treatment and monitoring have been explored and commented. Expert commentary : Knowing patient's complete HBV serostatus is mandatory in order to choose between treatment, prophylaxis or a pre-emptive approach. Recent guidelines favor treatment with high barrier molecules in all patients with chronic HBV infection and long lasting prophylaxis with those with inactive or resolved one. With regard to HCV, the new direct-acting antiviral agents have been safely administered in the hematological setting. Their use as first-line single treatment in indolent lymphomas, and combined with chemotherapy in aggressive ones, should be considered. Due to the existing risk of chronic HEV infection in the immunocompromised, screening with serum HEV-RNA should be performed in case of signs and symptoms indicative of hepatitis. In the event of HEV infection, reduction of immunosuppression and, if not feasible or unsuccessful, ribavirin treatment should be prescribed.